Campanhas de vestibular no Facebook: uma abordagem mercadol??gica e semi??tica - Porto, Detley Moreira (2015)
This dissertation investigates the influence of Advertising Campaigns of Vestibular three higher education institutions private of Bras??lia (Catholic University of Bras??lia UCB, University Center ??? UNIEURO and College Projection), on Facebook, as well as with the media society and massive, which accesses social networks today. In addition, other institutions are also referenced, in particular the forms of interaction of their advertising campaigns to the public that will take entrance exams in order to see how this type of hype exerts its effects on academic audience. To study the influence of advertising campaigns is the need to check which factors contribute to the choice of a Higher Education Institution (HEI), by students. The evolution of information technology has caused great impact and changing the mode of communication of the human being, which the field of higher education is also impacted, as educational organizations have to follow the changes in the market, however adapt to them while competitive strategy. It can be concluded that the vestibular advertising campaigns posted on the social network Facebook of the surveyed HEI, not present compelling content to the perception of the relevant public, representing little interactivity and almost no engagement features that could establish a relationship of dialogue advocated by semiotic theory Peirce.